Cathepsin G, a Neutrophil Protease, Induces Compact Cell-Cell Adhesion in MCF-7 Human Breast Cancer Cells. (10th November 2009) - Kudo, Tomoya; Kigoshi, Hideaki; Hagiwara, Takashi; Takino, Takahisa; Yamazaki, Masatoshi; Yui, Satoru
Abstract : Cathepsin G is a serine protease secreted by activated neutrophils that play a role in the inflammatory response. Because neutrophils are known to be invading leukocytes in various tumors, their products may influence the characteristics of tumor cells such as the growth state, motility, and the adhesiveness between cells or the extracellular matrix. Here, we demonstrate that cathepsin G induces cell-cell adhesion of MCF-7 human breast cancer cells resulting from the contact inhibition of cell movement on fibronectin but not on type IV collagen. Cathepsin G subsequently induced cell condensation, a very compact cell colony, resulting due to the increased strength of E-cadherin-mediated cell-cell adhesion. Cathepsin G action is protease activity-dependent and was inhibited by the presence of serine protease inhibitors. Cathepsin G promotes E-cadherin/catenin complex formation and Rap1 activation in MCF-7 cells, which reportedly regulates E-cadherin-based cell-cell junctions. Cathepsin G also promotes E-cadherin/protein kinase D1 (PKD1) complex formation, and Go6976, the selective PKD1 inhibitor, suppressed the cathepsin G-induced cell condensation. Our findings provide the first evidence that cathepsin G regulates E-cadherin function, suggesting that cathepsin G has a novel modulatory role against tumor cell-cell adhesion.